Cryptic Species from Biodiversity Hotspot: Estimation of Decapoda on Dead Coral Head Pocillopora in Raja Ampat Papua - Eka Maya Kurniasih; Andrianus Sembiring; Ni Putu Dian Pertiwi; Aji Wahyu Anggoro; Ni Kadek Dita Cahyani; Muhammad Dailami; Ambariyanto Ambariyanto; Diah Permata Wijayanti; Christopher P. Meyer (Marine Science Department Diponegoro University, 2020)
Cryptic organisms that live within the interstices of reef habitats contribute significantly to coral reef biodiversity. One example of this cryptic biodiversity is the high abundance of decapods in dead coral heads that associated with various biota. However, this diversity poorly studied especially species identification and species richness. This study aims to estimate the decapods diversity in Raja Ampat, Papua, using Pocillopora dead coral head method as semi-quantitative sampling approach. Raja Ampat in Papua is chosen because it situated in the center of Coral Triangle marine hotspot. Data were collected from 10 dead coral heads of genus Pocillopora from 10-meter depth near the islands of Kri and Misool. This study observed a total of 205 individuals Decapoda from Kri Island and 672 Individual from Misool Islands. Species richness observation (Chao1 and ACE) of the total samples reports only 11 families of decapoda detected in this study. Rarefaction curve reach an asymptote after all after all ten dead coral were analyzed; indicating that additional sample collection would not change estimates of diversity found in this study. The Shannon-Wiener index diversity on the Kri Island showed lower diversity value (2.09) compared to Misool Island (2.18). In the future, this research can be used as a basis for understanding the diversity of coral reefs as well as for management and conservation of coral reef ecosystems.